2001
DOI: 10.1038/sj.bmt.1703132
|View full text |Cite
|
Sign up to set email alerts
|

Serum cardiac troponin I levels and ECG/Echo monitoring in breast cancer patients undergoing high-dose (7 g/m2) cyclophosphamide

Abstract: Summary:High-dose cyclophosphamide (HD-CTX) is largely employed in high-dose chemotherapy (HD-CHT) protocols. HD-CTX dose-limiting toxicity expresses itself as cardiac toxicity which is fatal in a minority of patients. The pathophysiology of HD-CTX-associated cardiotoxicity is still poorly understood. Autopsy studies in patients who died from acute HD-CTX-induced cardiac toxicity revealed hemorrhagic myocardial cell death and interstitial edema. Recently troponins, in particular troponin I (cTnI), have been fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
54
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(64 citation statements)
references
References 32 publications
6
54
0
Order By: Relevance
“…HD thiotepa has been associated with a 5% cardiac toxicity in two studies, 54,55 while other series did not confirm these findings. 8,25 HD ifosfamide cardiotoxicity is reported in only two studies more than 20 years old. 56,57 Anecdotal evidence is reported for HD carmustine-associated cardiac toxicity.…”
Section: Other Chemotherapeutic Agentsmentioning
confidence: 99%
See 3 more Smart Citations
“…HD thiotepa has been associated with a 5% cardiac toxicity in two studies, 54,55 while other series did not confirm these findings. 8,25 HD ifosfamide cardiotoxicity is reported in only two studies more than 20 years old. 56,57 Anecdotal evidence is reported for HD carmustine-associated cardiac toxicity.…”
Section: Other Chemotherapeutic Agentsmentioning
confidence: 99%
“…8,10,17,18,26,[76][77][78][79] On the other hand, Steinherz et al 22 observed that HD cyclophosphamide-associated cardiac damage was most frequent in pediatric patients receiving cyclophosphamide X170 mg/kg or in those receiving X120 mg/kg who had received X100 mg/m 2 anthracyclines prior to transplant. Other authors found a trend towards significance also.…”
Section: Previous Anthracycline Exposurementioning
confidence: 99%
See 2 more Smart Citations
“…CY-induced myocarditis increases blood levels of cardiac enzymes (e.g. CK, CK-MB, and troponin-I), however, these parameters can not predict the early phase of cardiotoxicity (8). Recently, the noninvasive method of cardiac magnet resonance imaging (MRI) has proved useful for evaluating LV function and contrast enhancement of cardiac MRI may detect myocardial interstitial edema (9).…”
mentioning
confidence: 99%